2021
DOI: 10.1021/acs.jpcb.1c04517
|View full text |Cite
|
Sign up to set email alerts
|

Excited-State Lifetimes of DNA-Templated Cyanine Dimer, Trimer, and Tetramer Aggregates: The Role of Exciton Delocalization, Dye Separation, and DNA Heterogeneity

Abstract: DNA-templated molecular (dye) aggregates are a novel class of materials that have garnered attention in a broad range of areas including light harvesting, sensing, and computing. Using DNA to template dye aggregation is attractive due to the relative ease with which DNA nanostructures can be assembled in solution, the diverse array of nanostructures that can be assembled, and the ability to precisely position dyes to within a few Angstroms of one another. These factors, combined with the programmability of DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
90
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(105 citation statements)
references
References 70 publications
15
90
0
Order By: Relevance
“…Atomic charges for the dyes were calculated using the HF/6-31G* theory level [ 80 ]. The 26-basepair dsDNA duplex sequence and dye locations from Huff et al [ 29 ] was used. The dye–DNA structures were solvated in TIP3P water [ 81 ] in a truncated octahedron box with 1.2 nm between the dye–DNA structure and the box edge.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Atomic charges for the dyes were calculated using the HF/6-31G* theory level [ 80 ]. The 26-basepair dsDNA duplex sequence and dye locations from Huff et al [ 29 ] was used. The dye–DNA structures were solvated in TIP3P water [ 81 ] in a truncated octahedron box with 1.2 nm between the dye–DNA structure and the box edge.…”
Section: Methodsmentioning
confidence: 99%
“…Mg 2+ ions were used to neutralize the system. Cannon et al and Huff et al showed, experimentally, that by adding excess MgCl 2 to solutions containing DNA duplexes with two pentamethine indocyanine Cy5 dyes, DNA Holliday junctions could be formed [ 28 , 29 ]. Because of this, no excess MgCl 2 was used in the MD simulations apart from replacing a necessary number of water molecules with Mg 2+ to achieve neutral charge.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To gain additional insights into packing and coupling in the transverse dimer, we modeled its absorption and CD spectra. Specifically, we employed an approach based on Kühn–Renger–May (KRM) theory, 65 which we have previously used to derive information about packing and coupling in dimer, trimer, and tetramer aggregates of Cy5, 25 , 40 , 46 Square-660 (an indolenine-based squaraine), 52 and SeTau-670 (an aniline-based squaraine rotaxane). 38 Consistent with our expectations of H-aggregation, the modeling indicates that the “oblique” angle, α, between dyes (as the TDM is oriented along the long axis of the dye) is ∼22° ( section S9 ).…”
mentioning
confidence: 99%
“…More broadly, the results indicate that the transverse heterodimer solution is heterogeneous and includes a small subpopulation of monomers, likely as a result of either static or dynamic heterogeneity. 25 Here, because of the optical selectivity of the constituent dye monomers, such heterogeneity—albeit not a major contributor for the 615 nm pumping experiment—is immediately apparent when pumping the transverse dimer solution at 650 and 690 nm.…”
mentioning
confidence: 99%